Pengaruh Disiplin Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan PT. Corintek Inti Sejahtera Kota Bekasi - Angelina Simorangkir; Agus Dharmanto; Nita Komala Dewi (Jurnal Riset dan Inovasi Manajemen, 2024)
This research aims to determine the influence of work discipline and work environment on employee performance at PT. Corintek Inti Sejahtera Bekasi City. The type of research used in this research is quantitative research. The sampling technique used a saturated sampling technique through a questionnaire created via Google Form with the criteria of all 84 employees PT. Corintek Inti Sejahtera Bekasi City. The data analysis method uses multiple linear regression. The data was processed using IBM SPSS Statistics 23. The results of this study show that (1) Work discipline has a significant effect on employee performance at the PT. Corintek Inti Sejahtera Bekasi City, (2) The work environment has a significant effect on employee performance at the PT. Corintek Inti Sejahtera Bekasi City and (3) Work Discipline and Work Environment simultaneously influence employee performance at the PT. Corintek Inti Sejahtera Bekasi City.